Combination therapy of midodrine and droxidopa for refractory hypotension in heart failure with preserved ejection fraction per a pharmacist's proposal: a case report - Yuki Asai; Tomoaki Sato; Daisuke Kito; Takanori Yamamoto; Iwao Hioki; Yasuhisa Urata; Yasuharu Abe (BMC, 2021)
Abstract Background Patients with chronic heart failure (CHF) are often treated using many diuretics for symptom relief; however, diuretic use may have to continue despite hypotension development in these patients. Here, we present a case of heart failure with preserved ejection fraction (HFpEF), which is defined as ejection fraction ≥50% in CHF, and refractory hypotension, which was treated with midodrine and droxidopa to normalize blood pressure. Case presentation The patient was a 62-year-old man with a history of HFpEF due to mitral regurgitation and complaints of dyspnea on exertion. He had been prescribed multiple medications at an outpatient clinic for CHF management, including azosemide 60 mg/day, bisoprolol 2.5 mg/day, enalapril 2.5 mg/day, spironolactone 50 mg/day, and tolvaptan 15 mg/day. The systolic blood pressure (SBP) of the patient remained at 70-80 mmHg because the use of the diuretic could not be reduced or discontinued owing to edema and weight gain. He was hospitalized for the exacerbation of CHF. Although midodrine 8 mg/day was administered to improve hypotension, the SBP of the patient increased only up to 90 mmHg. On the 35th day after hospitalization, the urine volume decreased significantly (< 100 mL/day) due to hypotension. When droxidopa 200 mg/day replaced intravenous noradrenaline on the 47th day, the SBP remained at 100-120 mmHg and the urine volume increased. Conclusions Oral combination treatment with midodrine and droxidopa might contribute to the maintenance of blood pressure and diuretic activity in HFpEF patients with refractory hypotension. However, further long-term studies evaluating the safety and efficacy of this combination therapy for patients with HFpEF are needed.